Immunoregulatory Roles of Extracellular Vesicles and Associated Therapeutic Applications in Lung Cancer - Yin, Zhengrong; Fan, Jinshuo; Xu, Juanjuan; Wu, Feng; Li, Yang; Zhou, Mei; Liao, Tingting; Duan, Limin; Wang, Sufei; Geng, Wei; Jin, Yang (Frontiers in Immunology, 2020)
Lung cancer represents a fatal condition that has the highest morbidity and mortality among malignancies. The currently available treatments fall short of improving the survival and quality of life of late-staged lung cancer patients. Extracellular vesicles (EVs) secreted by tumors or immune cells transport proteins, lipids, and nucleic acids to other cells, thereby mediating immune regulation in tumor microenvironment. The cargoes carried by EVs vary with cellular state or extracellular milieu. So far, multiple studies have suggested that EVs from lung tumor cells (TEVs) or immune cells promote tumor progression mainly through suppressing antitumor immunity. However, modified or engineered EVs can be used as vaccines to elicit antitumor immunity. Besides, blocking the function of immunosuppressive EVs and using EVs carrying immunogenic medicines or EVs from certain immune cells also shows great potential in lung cancer treatment. To provide information for future studies on the roles of EVs in lung cancer immunity, this review focus on the immunoregulatory roles of EVs and associated treatment applications in lung cancer.